Sport Marketing, Marketing of Sport, and Its Challenges: A Review - Getnet, Daniel (Indonesian Journal of Sport Management, 2024)
Sports marketing significantly influences sport development by promoting a healthy sport ecosystem, attracting investment, and increasing event popularity, enabling marketers to utilize sports' attention for brand promotion. Despite numerous studies conducted in different parts, segments, and levels of sport marketing, the findings have been inconclusive, unidirectional, and contradictory. Therefore, the purpose of this review was to synthesize the existing research on sport marketing and marketing through sport. A total of 546 articles were initially identified from Google scholar database. These articles went through a rigorous review process, and 495 articles were excluded at different stages based on the inclusion criteria. The remaining 53 published materials that met the inclusion criteria were thematically synthesized to identify common themes and patterns. These are crucial ingredients in understanding the dynamics sport marketing and marketing of sport. This review enhances sport marketing discourse and lays the groundwork for future research, enabling a comprehensive study on current practices, issues, and possibilities at discipline, local, regional, continental, and international levels.